2022
DOI: 10.1177/00368504221076823
|View full text |Cite
|
Sign up to set email alerts
|

The training needs of critical care nurses: A psychometric analysis

Abstract: Background/Objective: Nurses develop the care methods they learn through specific training and this enables them to provide care in a safe, effective and efficient manner. Intensive Care Units (ICU), as complex areas in terms of care, require nurses with specific training. Due to this fact, we set ourselves the objective to validate a questionnaire that detects the training needs of intensive care nurses in Spain. Methods: A cross-sectional descriptive study, using an electronic questionnaire, adapted and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
4
0
4
Order By: Relevance
“…It is different from a previous study [ 37 ]. Those factors belong to nursing training [ 38 ]. Research reported that the higher level of professional identity related to nursing training [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is different from a previous study [ 37 ]. Those factors belong to nursing training [ 38 ]. Research reported that the higher level of professional identity related to nursing training [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…note that nurses need to develop their own competency including the most technical aspects, in addition to comprehensive care [ 31 ]. This development must incorporate the domains of knowledge that critical care nurses need to be fully educated [ 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a similarity between the majority demand for specialised training and the assessment of training needs, which determine that critical care nurses require specific training [ 41 ], and that the current model is not effective [ 24 ]. Health care systems and scientific associations need to develop a framework that includes the skills, abilities and knowledge that ICU nurses require to effectively care for critically ill patients [ 17 , 19 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleh karena itu, perawat yang bekerja di ruang intensif senantiasa harus melakukan pembaharuan untuk menunjang ilmu pengetahuan yang terbaru terkait perawatan pasien di ICU (Fouilloux et al, 2018). Perawat dapat mengembangkan skills yang dibutuhkan melalui pelatihan-pelatihan spesifik yang dapat membuat perawat mampu untuk menyediakan pelayanan kesehatan yang aman, efektif dan efisien terutama di area kritis dan kompleks seperti ICU (Santana-Padilla et al, 2022).…”
Section: Hasil Penelitian Dan Pembahasanunclassified